TA-1 Impact of Tea and Coffee Consumption on Stroke and Parkinson Disease: A Sri Lankan Perspective - Attanayake, M.K.D.K.; Amaratunga, D.; Gamage, R.; Ragunathan, M.K.; Fernando, H.; Liyanage, J.; Kulthunga, A.; Gunasekara, H.; Dissanayake, L.; Suriyakumara, S.V.T.; Udawatte, N.S.; De Silva, K.R.D. (Federation of Asian-Oceanian Neuroscience Societies, 2015)
Attached.
Keywords: stroke; PD; tea; coffee; smoking